First-Principles Calculations of the Electronic Structures and Optical Properties of Mg- and Sr-Doped $CaF_2$ (Journal of Atomic and Molecular Sciences, 2014)
Based on the density functional theory (DFT), the first-principles methodsare used to study and compare the electronic structures and optical properties of Mg-,Sr-doped $CaF_2$ systems with those of $CaF_2$ bulk in detail. In contrast to $CaF_2$ bulk,the band gaps of doped systems become narrower and the new peaks of density statesappear. The orbital interactions between $Mg,$ $Sr$ atoms and $Ca$ atom are enhancednear the Fermi level, besides, the doped systems all show single dielectric propertiesand their absorption coefficients for ultraviolet light are reduced greatly, for $Ca_7SrF_{16}$ system, there is a small absorption peak at 25.44 eV. Compared with $CaF_2$ bulk, dopedsystems have much lower extinction coefficients and much higher light transmittancein the ultraviolet region. In addition, their reflection and loss peaks all display red shiftand the peak value reduce.